Physical Time Within Human Time - Gruber, Ronald P.; Block, Richard A.; Montemayor, Carlos (Frontiers in Psychology, 2022)
Abstract A possible solution is offered to help resolve the ‘two times problem’ regarding the veridical and illusory nature of time. First it is recognized that the flow (passage) of time is part of a wider array of temporal experiences referred to as manifest time, all of which need to be reconciled. Then, an information gathering and utilizing system (IGUS) model is used as a basis for a view of manifest time. The model IGUS robot of Hartle that solves the ‘unique present’ debate is enhanced with veridical and (corresponding) illusory components of not only the flow of time but also the larger entity of manifest time, providing a dualistic IGUS robot that represents all of the important temporal experiences. Based upon a variety of prior experiments, that view suggests that the veridical system is a reflection of accepted spacetime cosmologies and through natural selection begets the illusory system for functional purposes. Thus, there are not two opposing times, one outside and one inside the cranium. There is just one fundamental physical time which the brain developed, now possesses and is itself sufficient for adaption but then enhances. The illusory system is intended to provide a more satisfying experience of physical time, and better adaptive behavior. Future experiments to verify that view are provided. With a complete veridical system of temporal experiences there may be less need to reify certain temporal experiences so that the two times problem is less of a problem and more of a phenomenon.